Ex ante assessment of improved site specific, digital fertilizer recommendations for small-holder potato production in Rwanda - Pemsl, D.E.; Hareau, G.; Mudereri, B.T.; Vandamme, Elke (2024)
This study aims at estimating the potential benefits associated with the introduction of improved, site-specific fertilizer recommendations for (smallholder) potato production in Rwanda. For the ex-ante assessment, we quantify expected benefits using a standard partial economic surplus model computed over a 25-year period (2020-2044). The resulting benefits are compared with the costs of developing, implementing, and disseminating/maintaining the innovation in a cost-benefit analysis which yields the common summary measures of NPV and IRR. To address the equity dimension of this intervention, we also calculated the number of expected beneficiaries as well as the expected reduction in poverty. To test the sensitivity of our results, we ran a number of increasingly restrictive scenarios.